Integrated Innovation System At Vale: Conecting Business And R&D - Leandro Augusto Viana Teixeira; Adauto Caldara; Márcio Francisco Dill Junges (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2019)
Innovation in the mining industry is critical when facing ever growing challenges, like the need to increase safety, reduce social and environmental impact, deal with commodities price fluctuations among others. However, successful innovation is not only the product of technological innovation, but it is also dependent on Innovation Management, which consists of changing the way a company fosters innovation, creating a new structure able to leverage technology knowledge and the ability to convert this knowledge in value. This paper presents a restructure option for innovation that focus on R&D development linked to business needs and company strategy. This new system was approached based on four fundamental blocks for innovation management (Approach, Organization, Resources and Metrics), showing how the technology master plan and a management tool are able to bring together all aspects necessary for the proper operation of the system. The new system confirmed the importance of having the initiatives organized as innovation roadmaps, connecting techno-scientific development with the company needs through the use of KPIs that are relevant to the business.